Kendala-Kendala dalam Proses Penyidikan Tindak Pidana Kekerasan Seksual pada Wanita Penyandang Disabilitas di Wilayah Hukum Kepolisian Resor Ende - Mariela Nikita Putri; Heryanto Amalo; Rosalind Angel Fanggi (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
This study aims to find out and analyze the obstacles in the process of investigating sexual violence against women with disabilities in the jurisdiction of the Ende Resort Police This research is an empirical juridical research, with field study data collection techniques with interview studies and literature studies. The data obtained were then presented in a qualitative descriptive manner. The results of this study show that: (1) the obstacles experienced by the Ende Resort Police investigators come from various factors such as Legal Factors, namely the unavailability of examination operational standards for people with disabilities; Factors of Law Enforcement Officials, lack of understanding of the apparatus regarding disabilities, limited investigation budget, difficulty in finding witnesses; Facilities and Infrastructure factors, lack of accessibility of buildings and rooms and unavailability of sign language interpreters; Community Factor, the community is less cooperative and the perpetrator escapes. (2) Efforts made include: capacity training for investigating officers, provision of facilities and infrastructure, submission of additional fees, cooperation with the ranks of the Police in finding escaped criminal offenders, and approaches through socialization to the community.